Poisoning cause analysis among patients hospitalized in an emergency department - Gorgol, Adam; Rzońca, Patryk; Goniewicz, Mariusz; Bednarz, Kamil; Pawlak, Emilia; Hawrylewicz-Łuka, Agnieszka; Gałązkowski, Robert (Journal of Education, Health and Sport, 2019)
Consequences of using psychoactive substances are always negative. They cause not only physical and mental dependence, but also huge damage in the body in case of poisoning. The toxicity of these substances varies and depends on the type of chemical compound. The effects can be difficult to predict and often can pose a direct threat to life and health. The objective of this study was to analyse the causes and consequences of poisoning with psychoactive substances among patients hospitalized in the Emergency Department of Stefan Kardynał Wyszyński Province Specialist Hospital in Lublin within the period of one year (01.01.2016 - 31.12.2016). Our own study results showed that men and people living in urban areas were the patients most frequently admitted to the Emergency Department due to poisoning. Alcohol was the most common psychoactive substance used by the patients in the study group. Poisoning with anti-epileptic, sedative-hypnotic and psychotropic medications predominated among women, whereas alcohol and narcotics and psychodysleptic medications were the most frequent cause of poisoning among men.